Hepatoma cell-derived exosomal SNORD52 mediates M2 macrophage polarization by activating the JAK2/STAT6 pathway - Yaqiong Zhang; Bo Li; Wanhong Gu; Linna Fan; Xiaofan Wang; Meifen Xu; Minqi Zhu; Chong Jin (Discover Oncology)
Abstract Background A recent study revealed the oncogenic role of box C/D small nucleolar RNA 52 (SNORD52) in hepatocellular carcinoma (HCC) by facilitating the aggressive phenotypes of hepatoma cells. However, the potential role of exosomal SNORD52 in macrophage polarization during HCC progression remains poorly understood. Methods Exosomes were isolated from hepatoma cells. Western blotting and flow cytometry were performed to determine the levels of M2 macrophage polarization markers. SNORD52 expression was assessed using qRT-PCR. The levels of JAK2/STAT6 pathway-related proteins were analyzed using western blotting. Results SNORD52 was enriched in exosomes derived from hepatoma cells and in plasma samples from patients with HCC. Hepatoma cell-derived exosomal SNORD52 was internalized by THP-1 macrophages. SNORD52 overexpression increased the levels of M2 macrophage polarization markers and JAK2/STAT6 pathway-related proteins Additionally, hepatoma cell-derived exosomal SNORD52 interacted with the JAK2/STAT6 pathway to mediate M2 macrophage polarization. Conclusions Our findings revealed that hepatoma cell-derived exosomal SNORD52 induces M2 macrophage polarization by activating the JAK2/STAT6 pathway.